2017
DOI: 10.1016/j.vaccine.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a TLR7 agonist to an acellular pertussis vaccine enhances Th1 and Th17 responses and protective immunity in a mouse model

Abstract: a b s t r a c tA resurgence of whooping cough (pertussis) has been observed in recent years in a number of developed countries, despite widespread vaccine coverage. Although the exact reasons of the recurrence of pertussis are not clear, there are a number of potential causes, like antigenic variation in the circulating strains of Bordetella pertussis, changes in surveillance and diagnostic tools, and potential differences in protection afforded by current acellular pertussis (aP) vaccines compared to more rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 22 publications
0
29
1
1
Order By: Relevance
“…on days 0 and 28 with 1/5 the human dose of Boostrix alone or mixed with 30 g BcfA and then were challenged intranasally with Bp536 on days 12 to 14 postboost. We selected this dose of aPV since it has been used by others to test vaccine-induced immune responses in mice (20)(21)(22)(23). Bacterial colonies in the lungs were enumerated on days 1, 4, 7, and 14 postchallenge.…”
Section: Resultsmentioning
confidence: 99%
“…on days 0 and 28 with 1/5 the human dose of Boostrix alone or mixed with 30 g BcfA and then were challenged intranasally with Bp536 on days 12 to 14 postboost. We selected this dose of aPV since it has been used by others to test vaccine-induced immune responses in mice (20)(21)(22)(23). Bacterial colonies in the lungs were enumerated on days 1, 4, 7, and 14 postchallenge.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this inclusion of a TLR7 agonist with Alum re-directed the alum-induced Th2 flavoured response towards a more Th1-biased immune profile [60][61][62]. Using anionic liposomes, Fox et al…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous work reported that R848 has potential as a vaccine adjuvant owing to its ability to activate the immune response. Recent studies found that R848 treatment enhanced the immune response to pathogen challenge, arousing a long‐range immune response without influencing the original immunity. Here, R848 enhanced the cellular immune response of T. gondii antigen when used as an adjuvant for the pROP29 vaccine.…”
Section: Discussionmentioning
confidence: 99%